Mechanical properties and structural health monitoring performance of carbon nanotube-modified FRP composites: A review - Li Jianbin (De Gruyter, 2021)
Fiber-reinforced polymer composites are high-performance materials used extensively in aerospace and defense industries. Researchers have added various nanoscale materials to FRPs for improving their mechanical properties and to prepare multifunctional composites. Carbon nanotubes (CNTs) with their high strength, high modulus, and large aspect ratio have emerged as a frontrunner in the nano-reinforcements, and there is a large volume of published research on this topic. This article provides an extensive review of key publications covering topics of fabrication methods, enhancement of mechanical properties, and applications of CNT-modified FRP materials in structural health monitoring. A description of the main methods of adding CNTs into FRP materials, including dispersion in the resin and film lay-up, is presented. A key focus of the review is the effect of CNTs on the mechanical properties of FRP composites, including interlaminar fracture toughness, impact resistance, and fatigue properties. Since CNTs have self-sensing properties, there is potential to use CNTs for nondestructive identification (NDI) and structural health monitoring (SHM) of composite structures. Finally, a discussion of the problems that might be encountered during the use of CNTs as nano-reinforcements in FRP, and the future application potential of CNT-modified FRP materials is reported.